Descriptive Qualitative Content Analysis of Coastal Human Resource Management in the Blue Economy Perspective: A Literature Study - Fandy Yones Latuni; David Paul Elia Saerang; Djurwati Soepeno; Rudy S. Wenas (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to analyze the scientific literature on coastal-based human resource management from a blue economy perspective through a content analysis approach. This study employed a qualitative descriptive method with a PRISMA-based systematic literature review technique for 41 scientific articles obtained from Publish or Perish, published between 2020 and 2026. Data were analyzed through open coding, axial coding, and selective coding to identify key themes that represent the conceptual constructs in the literature. The results indicate six main themes in coastal-based human resource studies: coastal human resource capacity development, coastal community economic empowerment, blue economy implementation, governance and institutions, gender and social inclusion, and digital innovation and transformation. These findings demonstrate that coastal-based human resource management is a multidimensional concept that focuses not only on improving individual capacity but also encompasses institutional, social, economic, and environmental sustainability aspects. This study also produced a conceptual model demonstrating that the successful implementation of the blue economy is highly dependent on the integration of capacity building, community empowerment, and institutional governance, supported by innovation and social inclusion. Theoretically, this study expands the study of human capital in the context of sustainable coastal development. Practically, the results of this study can serve as a basis for formulating more adaptive, inclusive, and sustainable coastal human resource development policies.